The global governed? : refugees as providers of protection and assistance / Kate Pincock, Alexander Betts, Evan Easton-Calabria. - Pincock, Kate, 1987-; Betts, Alexander, 1980-; Easton-Calabria, Evan Elise (Cambridge asylum and migration studies., 2020)
When refugees flee war and persecution, protection and assistance are usually provided by United Nations organisations and their NGO implementing partners. In camps and cities, the dominant humanitarian model remains premised upon a provider-beneficiary relationship. In parallel to this model, however, is a largely neglected story: refugees themselves frequently mobilise to create organisations or networks as alternative providers of social protection. Based on fieldwork in refugee camps and cities in Uganda and Kenya, this book examines how refugee-led organisations emerge, the forms they take, and their interactions with international institutions. Developing an original theoretical framework based on the concept of 'the global governed', the book shows how power and hierarchy mediate the seemingly benign notion of protection. Drawing upon ideas from anthropology and international relations, it offers an alternative vision for more participatory global governance, of relevance to other policy-fields including development, humanitarianism, health, peacekeeping, and child protection.